PENGARUH PENYULUHAN TERHADAP PENGETAHUAN DAN PRAKTIK GIZI SEIMBANG PADA ANAK SEKOLAH DASAR - Thresia Dewi Kartini; Manjilala Manjilala; Suri Etika Yuniawati (Jurusan Gizi Poltekkes Kemenkes Makassar, 2019)
Nutrition counseling using the slogan 4 Healthy 5 Perfect since 1952, began to undergo changes into the General Guidelines for Balanced Nutrition (PUGS) in 1992. Counseling about health and nutrition to the community is not an easy thing because it involves behavior change. Reduced knowledge will also reduce a person's ability to apply nutritional information to everyday life. School children are the next generation of the nation and constitute development capital, so that their health needs to be improved. This study aims to determine the effect of counseling on balanced nutrition knowledge and practices in children of Mandai Elementary School in Makassar City. This study wanted to see the effect of balanced nutrition counseling on a group before and after intervention. This research is an analytical study with quasi-experimental design (quasi experimental), one group pretest posttest design approach. The sample is the fifth grade students in the Mandai Elementary School in Makassar City who were selected by simple random sampling of 46 samples. Data on balanced nutrition knowledge and balanced nutrition practices before and after counseling were obtained through interviews using questionnaires. Data analysis using the Wilcoxon test. Data is presented using tables and narratives.The results showed that there was an influence of knowledge (p = 0,000) and balanced nutrition practices (p = 0,001) of school children before and after counseling. It is recommended for schools, especially teachers, to be able to socialize repetitive balanced nutrition guidelines through empowering School Health Enterprises (SHE).